CHRONIC CENTRAL SEROUS CHORIORETINOPATHY: Early and Late Morphological and Functional Changes After Verteporfin Photodynamic Therapy. Issue 5 (May 2019) - Iacono, Pierluigi; Tedeschi, Massimiliano; Boccassini, Barbara; Chiaravalloti, Adele; Varano, Monica; Parravano, Mariacristina
Abstract : Purpose: To describe early and late morphological and functional changes in subjects receiving photodynamic therapy (PDT) for chronic central serous chorioretinopathy. Methods: Patients with chronic central serous chorioretinopathy were prospectively enrolled and received standard PDT. At the baseline examination, each subject underwent complete ophthalmological examination, including best-corrected visual acuity (BCVA) assessment, fluorescein angiography and indocyanine green angiography, spectral domain optical coherence tomography, and microperimetry. Spectral domain optical coherence tomography, microperimetry, and BCVA assessment were repeated in multiple sections over 7 days after PDT and at 1-, 3-, and 12-month intervals. Main outcome measures were: identification of early changes (1-week examination) in BCVA, retinal sensitivity, and spectral domain optical coherence tomography parameters and their influence on outcomes at the 1-year follow-up. Results: Three main patterns of early response to PDT were identified during the 1-week examination. The neurosensory retinal detachment most frequently decreased rapidly (12/19 pts), with complete resolution in 50% of cases. An increase in neurosensory retinal detachment height was registered in 16% (3/19) of cases, whereas in 21% (4/19), a large fluctuation in neurosensory retinal detachment was encountered. Best-corrected visual acuity declined significantly in 5/12 patients in the first group and was stable or improved in the remaining cases. Overall, retinal sensitivity diminished in 16/19 subjects, with a mean worsening of 2.56 dB ( P = 0.0002). At the 12-month examination, final mean BCVA improved by 14.4 letters ( P = 0.001) and a similar progressive recovery in the retinal sensitivity was observed (+2.69 dB, P = 0.0039). The neurosensory retinal detachment completely resolved in 18/19 (95%) cases, with a parallel significant reduction in central foveal choroidal thickness ( P < 0.0001). Conclusion: Three patterns of early response to standard PDT can be identified. Although an early and abrupt reduction in BCVA and retinal sensitivity after treatment is possible, this does not compromise a final improvement in visual functions. Abstract : The current prospective study investigates the early and late morphological and functional changes in subjects receiving standard photodynamic therapy with verteporfin for chronic central serous chorioretinopathy. Three main patterns of early response to photodynamic therapy were identified during the 1-week examination, ranging from a complete resolution of the neurosensory detachment to an increase in fluid collection; the changes were predominantly associated with a reduction in retinal sensitivity. Despite the variability of the early changes, a complete resolution of the fluid collection, with recovery of retinal sensitivity, was observed in 95% of cases at the 1-year examination.